Identifying strokes in Nigerian children with sickle cell disease as part of clinical trials: training curriculum for healthcare professionals in low-income settings - Ghafuri, Djamila L.; Bello-Manga, Halima; Kirkham, Fenella J.; Ciobanu, Mariana; Trevathan, Edwin; Rodeghier, Mark; DeBaun, Michael R.; Jordan, Lori C. (Frontiers in Stroke, 2025)
Introduction Nigeria has the highest proportion of children with sickle cell anemia (SCA) globally; without transcranial Doppler screening and ongoing treatment (regular blood transfusions or hydroxyurea therapy), 10% will have a stroke in childhood. In low-resource settings, training to recognize and prevent strokes in children with SCA is vital. A sustainable Sickle Cell Disease Stroke Prevention Teams program was established, as part of clinical trials, to address the need for stroke care in northern Nigeria. We describe our health professional stroke training curriculum and specific application to detect strokes in clinical trials in low-resource settings. Methods Children aged 5–12 and 2–16 years with SCA in northern Nigeria were enrolled in the SPRING and SPRINT primary and secondary stroke prevention trials, respectively. The primary outcome measure in both trials was a clinical stroke based on the World Health Organization definition. Non-neurologist physicians were trained in-person and via video lectures regarding stroke recognition, performing neurological examinations using the adapted Pediatric NIH Stroke Scale, and acute stroke care. Central stroke adjudicators, two pediatric neurologists, reviewed the case report forms and recorded videos of the neurological examinations. Results Six physicians completed the curriculum at three sites and were certified to detect strokes. Of 20 children with suspected stroke, 8 and 11 children had acute initial or acute recurrent strokes confirmed in the SPRING (N = 220) and SPRINT (N = 101) trials, respectively. The concordance rate between local stroke diagnoses and the central stroke adjudication process was 95% (19 of 20). One child presented with non-specific symptoms and hypertonia and was mislabeled locally as an acute stroke. Discussion A curriculum to train healthcare providers in pediatric acute stroke recognition and care in a low-resource setting is feasible and sustainable. We successfully identified strategies for task shifting from a single pediatric neurologist in the region to multiple non-neurologist physicians.